Fine-tuning the coordination atoms of copper redox mediators: an effective strategy for boosting the photovoltage of dye-sensitized solar cells. Issue 20 (9th May 2019) - Zhao, Yawei; Shen, Junyu; Yu, Ze; Hu, Maowei; Liu, Chong; Fan, Jiandong; Han, Hongxian; Hagfeldt, Anders; Wang, Mei; Sun, Licheng
Abstract : Herein, we report a new class of copper complexes bearing a tetradentate polythioether ligand, [(S4 )Cu] 2+/+ (1 2+/+, S4 = 1, 4, 8, 11-tetrathiocyclotetradecane), as a redox mediator in dye-sensitized solar cells (DSCs). Abstract : Natural systems have marvelously utilized copper complexes featuring sulfur-coordinating ligands, known as blue copper proteins, as efficient electron-transfer mediators in biological processes. Copper complexes with sulfur-coordinating ligands have been attempted as redox mediators in dye-sensitized solar cells (DSCs), the performance of which is not yet satisfactory and still remains less well explored. Herein, we report the application of new copper complexes bearing a tetradentate polythioether ligand, [(S4 )Cu] 2+/+ (1 2+/+, S4 = 1, 4, 8, 11-tetrathiocyclotetradecane), as a redox mediator in DSCs in comparison with its N4 -tetradentate counterpart [(N4 )Cu] 2+/+ (2 2+/+, N4 = 1, 4, 8, 11-tetramethyl-1, 4, 8, 11-tetraazacyclotetradecane). Impressively, the changes of coordination atoms from N to S positively shift the formal redox potential of the copper complexes by 600 mV, leading to a remarkably high photovoltage approaching 1.0 V. This is one of the highest photovoltage values reported thus far for DSCs based on copper redox mediators.